Disseminated abdominal tuberculosis, an unusual presentation in a healthy adolescent: a case report - Sahagun, Cesar Manuel Vargas; López, Elsa Paulina Alonso; Vela, Cuauhtémoc Morfín (International Journal of Research in Medical Sciences, 2022)
Disseminated abdominal tuberculosis is a rare and highly complex disease. With a very low incidence of 2.5% of patient with extrapulmonary tuberculosis and no detected in a timely manner reaches up to a mortality of 8%. We present a rare case of disseminated abdominal tuberculosis in an adolescent that began as a splenic abscess managed with open surgery and clinical-surgical finding of disseminated tuberculosis in the abdominal cavity.